2022
DOI: 10.3390/rs14030598
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Dynamics of National Characteristic Towns in China Using Nighttime Light Data

Abstract: Characteristic towns have emerged along with China’s economic and social development. As a new model of small-town development, they have played an essential role in promoting industrial transformation and upgrade, improving the living environment, and promoting regional innovation and development. Accurate identification of the expansion characteristics of National Characteristic Towns (NCTs) is vital for optimizing the spatial layout of characteristic towns and adjusting the policies of characteristic towns.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Urban expansion covers a variety of factors, and the increase of urbanization level and economic development have an important impact on urban expansion. The urban development in the YB is uneven, and the level of economic development varies greatly among cities [3]. Based on the reality, the expansion of cities with developed economy, convenient transportation and high population density is more significant [28][29][30]36], and the results of this paper found that the difference in expansion between provincial capital cities and non-capital cities, as well as between upper and middle and lower reaches of cities due to economic and social factors, is significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urban expansion covers a variety of factors, and the increase of urbanization level and economic development have an important impact on urban expansion. The urban development in the YB is uneven, and the level of economic development varies greatly among cities [3]. Based on the reality, the expansion of cities with developed economy, convenient transportation and high population density is more significant [28][29][30]36], and the results of this paper found that the difference in expansion between provincial capital cities and non-capital cities, as well as between upper and middle and lower reaches of cities due to economic and social factors, is significant.…”
Section: Discussionmentioning
confidence: 99%
“…Urban spatial expansion is an important symbol of urbanization, and the study of UB area expansion is of great significance to identify the urbanization process and judge the urban development stage. Simultaneously, the development of remote sensing and geoinformation technology has led to the innovation of urban expansion detection technology, and the emergence of NTL data has, to a certain extent, made it possible for urban studies to conduct multi-scale, largescale, and long-time period urban expansion detection [1,2], and it also has the advantages of large coverage, fast timeliness, and easy accessibility, which can be widely used in multi-scale and long-time period urban problem studies [3].…”
Section: Introductionmentioning
confidence: 99%